2020
DOI: 10.1136/esmoopen-2020-000947
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solid cancer on in-hospital mortality overall and among different subgroups of patients with COVID-19: a nationwide, population-based analysis

Abstract: BackgroundCancer seems to have an independent adverse prognostic effect on COVID-19-related mortality, but uncertainty exists regarding its effect across different patient subgroups. We report a population-based analysis of patients hospitalised with COVID-19 with prior or current solid cancer versus those without cancer.MethodsWe analysed data of adult patients registered until 24 May 2020 in the Belgian nationwide database of Sciensano. The primary objective was in-hospital mortality within 30 days of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 22 publications
(21 reference statements)
1
71
0
2
Order By: Relevance
“… 5 , 6 , 7 , 8 In a recent nationwide, population-based analysis in Belgium, it has been shown that solid cancer is an independent adverse prognostic factor for in-hospital mortality among patients with COVID-19. 9 Consequently, international and national guidelines from various oncological societies and hospitals have been developed to reduce the exposure of cancer patients to SARS-CoV-2 infection and diminish the impact of the pandemic upon health services for oncological diseases. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 In a recent nationwide, population-based analysis in Belgium, it has been shown that solid cancer is an independent adverse prognostic factor for in-hospital mortality among patients with COVID-19. 9 Consequently, international and national guidelines from various oncological societies and hospitals have been developed to reduce the exposure of cancer patients to SARS-CoV-2 infection and diminish the impact of the pandemic upon health services for oncological diseases. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Patients with cancer are at significantly increased risk of morbidity and death from COVID-19, with mortality estimates ranging from 11% to 40.5% across different studies. [1][2][3][4][5][6] This large range likely reflects the heterogeneity of these studies, with some including patients with inactive cancer versus only active cancer and some including only hospitalised patients. Although it is clear that COVID-19-related outcomes are poor in patients with cancer, the impact of anticancer therapy on these outcomes remains contentious.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies carried out around the world have shown that patients with cancer are at a higher risk for severe complications and mortality from SARS-CoV-2 infection [13][14][15][16][17][18][19]. In the scientific brief by the World Health Organisation (WHO) on July 11, 2020, the organisation acknowledged the possibility of airborne transmission in addition to the droplet, contact, fomite, faecal-oral, bloodborne, mother-to-child and animal-to-human transmission.…”
Section: Recommendations On Covid-19 Testing For Cancer Patientsmentioning
confidence: 99%